The Impact of Third Party Reproduction on Family and Kinship - Z Behjati Ardakani; M Navabakhsh; S Tremayne; MM Akhondi; F Ranjbar; AR Mohseni Tabrizi (JRI, 2021)
The development of in vitro fertilization (IVF) in the UK, in 1978, proved a major breakthrough in the process of human reproduction, which had remained constant in human history. The impact of IVF and the ensuing assisted reproductive technologies (ARTs) has not been limited in revolutionizing the "natural" practice of biological reproduction, but has reached out to and affected almost every institution in society. Family and kinship, as the social expression of reproduction and the institutions which are the most transparently structured realm of human life are those most profoundly affected by ARTs. Although literature on the implications of ARTs is in general abundant, this article presents new insights on their impact on family and kinship in Iran, which remains a unique case in the Muslim world. It explores the particular way ARTs, especially third-party donation, have been endorsed and practiced in Iran, and their consequences for the family, the infertile individuals, and their position vis-à-vis their kin and social group. The conclusion points to the lack of clarity concerning the initial rulings by the Islamic jurists, who allowed the practice of ARTs, and which has led to a number of unintended consequences regarding the legal, religious, cultural, and ethical issues, affecting the family, its structure and the relationship between the kin group. These consequences range, inter alia, from the question of the anonymity of third-party donor, to the permissibility of gamete donation between blood relatives, and to the absence of enforceable legislation.